A New Parameter for Erythropoiesis: The Relationship of Immature Reticulocyte Fraction Values in Cord Blood with Clinical Factors and Reference Values for Newborns - Dursun, Zarife Esra; Guzoglu, Nilufer; Kisa, Ucler; Davutoglu, Salih; Aliefendioglu, Didem (Duzce Univ, Fac Medicine, 2023)
Aim: The immature reticulocyte fraction (IRF) is a new parameter for the reticulocyte maturity index, representing an independent parameter of erythropoiesis that may be useful to better assess erythropoietic activity in neonates. In this study, the relationship between IRF values and clinical features in newborns was investigated and reference values were obtained. Material and Methods: Newborns between 28-40 weeks of gestation were included in this prospective study. At birth, maternal venous and cord blood samples were obtained for measurements of complete blood count (CBC), blood gases, and plasma concentrations of various biochemical parameters. Results: A total of 123 newborns, 99 term and 24 preterm, were included in the study. When the laboratory characteristics of the premature and term babies were compared according to their gestational weeks, while the median IRF value of cord blood was higher in term babies than in premature babies (p=0.039), other laboratory findings did not differ significantly. The median IRF value was 0.52 (range, 0.15-1.00) in term infants and 0.34 (range, 0.16-0.76) in preterm infants. IRF reference values for the term and preterm newborns were determined in cord blood. Moderately positive correlations were observed between the IRF levels and both the RDW (r=0.423, p<0.001) and the CRP (r=0.389, p<0.001) levels. Conclusion: The results of this study showed that newborns' IRF values were not affected by maternal variables and changed with the week of birth. The results of this study might be considered a guide for future studies using IRF value in newborns.
Keywords: Cord blood; newborn; immature reticulocyte fraction